Gilteritinib overcomes lorlatinib resistance in ALK-rearranged cancer - Hayato Mizuta; Koutaroh Okada; Mitsugu Araki; Jun Adachi; Ai Takemoto; Justyna Kutkowska; Kohei Maruyama; Noriko Yanagitani; Tomoko Oh-hara; Kana Watanabe; Keiichi Tamai; Luc Friboulet; et al. (Nature Communications, 2021)
Resistance to ALK inhibitors such as lorlatinib often arise due to on-target mutations. Here, the authors show the multi-kinase inhibitor gilteritinib is effective against different mutations that arise during lorlatinib in ALK fusion positive lung cancer to cause resistance.